A Cyclopeptide and a Tetrahydroisoquinoline Alkaloid from Ophiorrhiza nutans - Tadayoshi Onozawa (2018)
© 2017 The American Chemical Society and American Society of Pharmacognosy. A new cyclopeptide, ophiorrhisine A (1), a new tetrahydroisoquinoline alkaloid, 7′,10-dide-O-methylcephaeline (2), two known β-carboline alkaloids, and four known tetrahydroisoquinoline alkaloids were isolated from Ophiorrhiza nutans (Rubiaceae). Compound 1 is a tetrapeptide possessing a 14-membered paracyclophane ring and a novel N,N,N-trimethyltyrosine residue in the side chain. The stereochemistry at the aryl-alkyl ether bond was different from that of other known 14-membered paracyclophanes. The structure of 2 was established by spectroscopic analysis and semisynthesis.